Decoloniality Perspectives in Global Health Education: A Scoping Review (Revista Lusófona de Educação, 2026)
Global health education reflects the historical inequalities influenced by colonialism. Coloniality maintains hierarchies and limits the representation of local knowledge. Thus, considering local knowledge, decolonization is essential for reducing inequalities and making health systems more inclusive and equitable. This study aimed to understand the decolonization of global health education and describe the actions taken to ensure the effectiveness of the decoloniality process. This scoping review was conducted in accordance with the Joanna Briggs Institute guidelines. Specific descriptors were used in PubMed, SciELO, BVS, LILACS, and ScienceDirect databases. Articles and gray literature on the decolonial approach to global health education were included, as were studies published in English, Portuguese, and Spanish. Articles and gray literature for which data extraction was impossible were excluded, and 11 articles were selected for inclusion in the review. The results show that global health education still favors rich countries, excludes local knowledge, and centralizes resources and leadership. Notable initiatives include institutional partnerships, the inclusion of local perspectives in curricula, and funding for low- and middle-income countries. Strategies include training community workers and strengthening the representation of cultural minorities in social work. Therefore, decolonizing global health education requires reflection on the apparent dichotomy between decolonial approaches, which prioritize local and specific knowledge, and global perspectives, which seek broader and more universal solutions. The integration of this knowledge, educational diversification, and institutional cooperation is essential to overcome financial, political, and cultural barriers while respecting the diversity of contexts and experiences.